STABILITAS DIMENSI KAYU KARET (Hevea brasiliensis, Muell. Arg) BERDASARKAN POSISI KETINGGIAN PADA BATANG DAN SUHU PENGERINGAN - Sarman, .; Usman, Fadillah H; Nurhaida, . (JURNAL HUTAN LESTARI, 2017)
AbstractThis research was carried out in the Wood Workshop Faculty of forestry University of Tanjungpura to manufacture test and example in the lab Silvikultur for testing the stability of dimension lumber, Wood is a material that besifat hygroscopic materials that can absorb and remove water depending on the environment. The test sample is inserted into each of the oven with a temperature of 500C, 700C, and 900C until it weighs the constant. The purpose of this research is to know the influence of the position on the stem height and temperature of drying as well as the interaction of these two factors the dimension stability of wood against the Rubber as well as knowing the position on the stem height and the most appropriate drying temperature so that it can show the highest dimensional stability. The results of the research on the radial direction indicates that the value of moisture content ranged from 9.8394%-10.3484% increase of the drying temperature decreases. While the value of density showed no noticeable difference i.e. ranged from 0.8188%-0.7669%. Depreciation value dimensions vary greatly on the position of the height of the stem that is ranged from 1.2189%.-3.1405%. Research on tangential direction indicates that the value of moisture content ranged from 9.9894%-14.6225% increase of the drying temperature decreases. While the value of density showed no noticeable difference i.e. value 0.7390%-0.8143%. Value changes in dimensions ranging from 1.1594%-2.1629%. The value of depreciation is not too mean and very varied temperature drying.Keywords : Dimensional stability, temperatur drying , The height position on the rod